SAPAAN KEKERABATAN BAHASA KERINCI DI KECAMATAN GUNUNG RAYA KABUPATEN KERINCI - Viki Diyanti (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2021)
ABSTRACT This article aims to analyze the types of kinship greeting words in Kerinci language and social factors that influence the types of kinship greeting words in Kerinci language in Gunung Raya sub-district, Kerinci district. This research uses a qualitative approach with descriptive methods. The research data is the kinship greeting words in Kerinci language in Gunung Raya sub-district, Kerinci district. The research data comes from informants as native speakers of Kerinci language who live in Gunung Raya sub-district.The result of this study is the community kinship system of Gunung Raya sub-district based on matrilineal lineage, someone will follow the lineage of mother. The male becomes a kindred based on the marriage line. The kinship greeting words in Kerinci language in Gunung Raya sub-district based on the lineage consist of 25 greeting words, while the kinship greeting words in the Kerinci language in Gunung Raya sub-district based on the marriage line consist of 29 greeting words. Social factors that influence the form of kinship greeting words in Kerinci language in Gunung Raya sub-district are social distance, age, gender, social status, physical characteristics, and language contact. Keyword: greeting words; Kerinci language; kinship; Gunung Raya sub-district